A high-plasticity 1500MPa grade ultra-high strength steel and its preparation method
By optimizing the composition and process in 1500MPa grade ultra-high strength steel, using thin slab continuous casting and rolling and hot coil insulation cover treatment, the problem of insufficient elongation of existing ultra-high strength steel is solved, high plasticity and excellent forming performance are achieved, and manufacturing costs are reduced.
Patent Information
- Application Number
- CN202210735497.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-27
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2042-06-27
AI Technical Summary
The existing 1500MPa grade ultra-high strength steel has insufficient elongation and cannot meet the dual requirements of automobile safety performance and forming performance. At the same time, the manufacturing process is complex and the cost is high.
High plasticity 1500MPa grade ultra-high strength steel, whose components include C, Si, Mn, Cr, Al, Ti, B and other elements. The hot-rolled coil with the finished thickness is directly obtained through the thin slab continuous casting and rolling process, and the hot-roll insulation cover is processed, and finally the pickling and continuous annealing are carried out.
It achieves high plasticity, excellent surface quality and good welding performance of ultra-high strength steel, reduces the complexity and cost of manufacturing processes, and at the same time reaches ≥18%, which is suitable for automotive safety structural parts.
Smart Images

Figure CN117344201B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a high-strength steel manufacturing technology, and in particular to a high-plasticity 1500MPa grade ultra-high-strength steel and a manufacturing method thereof. Background Art
[0002] In recent years, advanced high-strength steel for automobiles has been widely used in the automobile manufacturing industry to reduce the weight of the vehicle body, save energy and reduce emissions, improve collision safety and reduce manufacturing costs. Advanced high-strength steel is currently the most competitive material for lightweighting the vehicle body by increasing the strength of the steel plate to reduce the thickness of the steel plate while maintaining excellent forming properties.
[0003] The ultra-high-strength martensitic steel with a strength of 1500MPa and a large usage has an elongation of about 5%, which can no longer meet the dual requirements of the automotive field for automobile safety performance and forming performance during the manufacturing process. Another type of steel with a large usage is hot-formed steel, but the forming process of hot-formed steel has high requirements for heating equipment and cooling capacity, the process is complicated, and its elongation is basically within 10%. The third-generation high-strength steel for automobiles has both high strength and high plasticity and is relatively low in cost. The strength-plasticity product can reach 20-30GPa%, which has attracted widespread attention.
[0004] Chinese patent publication number CN103667884B discloses "1400MPa grade low yield ratio high elongation cold-rolled ultra-high strength automobile steel preparation method", whose composition is: C 0.14% ~ 0.16%, Si1.31% ~ 1.51%, Mn 2.7% ~ 2.9%, S ≤ 0.005%, P ≤ 0.009%, Al 0.11% ~ 0.51%, RE 0.005-0.20%, the balance is Fe and unavoidable impurities. The composition design of this patented steel is only simple C, Si, Mn, Al and a small amount of rare earth elements, and the manufacturing process is conventional casting-hot rolling-cold rolling-continuous annealing. The finished steel structure accounts for 70-85% martensite, 5-20% residual austenite, and a small amount of ferrite, but the tensile strength of the invented steel is at the 1400MPa level, the elongation is greater than or equal to 8%, and the yield strength is low.
[0005] Chinese patent publication number CN106244918B discloses "a 1500MPa grade high-strength and plasticity automotive steel and its manufacturing method". The composition of this patented steel is: C 0.1-0.3%, Si 0.1-2.0%, Mn 7.5-12%, Al 0.01-2.0%, and its chemical elements also have at least one of Nb 0.01-0.07%, Ti 0.02-0.15%, V 0.05-0.20%, Cr 0.15-0.50%, Mo 0.10-0.50%, and the remainder is iron and other inevitable impurities. The manufacturing method includes the following steps: 1) smelting and casting; 2) hot rolling; 3) bell furnace annealing, annealing temperature is 600-700℃, annealing time is 1-48h; 4) cold rolling; 5) first annealing after cold rolling: annealing temperature is between Ac1 and Ac3 temperature, annealing time is greater than 5min; 6) second annealing after cold rolling: annealing temperature is 750-850℃, annealing time is 1-10min; 7) tempering: tempering temperature is 200-300℃, tempering time is not less than 3min. The microstructure of the 1500MPa grade high strength and plasticity product automotive steel is austenite + martensite + ferrite or austenite + martensite, and its strength and plasticity product is not less than 30GPa%. Although the patent can obtain a better strength and plasticity match, the manufacturing process is extremely complicated, and the high Mn content in the composition also has high difficulty in manufacturability.
[0006] Chinese patent publication number CN106917055B discloses "a third generation high-strength and toughness automobile steel and its preparation method", whose composition is: C 0.40-0.60%, Si 1.00-2.00%, Mn 1.5-3.0%, Ni 0-0.60%, Cr0.50-1.50%, Mo 0.30-0.60%, V 0-0.20%, Co0-1.50%, Al 0-1.50%, the balance is Fe and inevitable impurities. After vacuum smelting, casting is carried out, and then hot rolling is carried out with a total reduction rate of 80%-95%. The obtained hot-rolled plate is heated to 900-970℃ at a speed of 5-20℃ / s for austenitization for 10-20min, and then air-cooled to 250-320℃ for 2-12h. The yield strength of the material exceeds 1000MPa, the tensile strength exceeds 1500MPa, and the elongation after fracture exceeds 20%. The patent mainly involves an ultra-high strength bainitic steel with a complex composition containing a large number of alloy elements, and the heat treatment process is inefficient, the austenitization temperature is too high, and the low-temperature treatment time is too long.
[0007] Chinese patent publication number CN108018484A discloses "a cold-rolled high-strength steel with a tensile strength of more than 1500MPa and excellent formability and a method for manufacturing the same". The composition of the patented steel is: C 0.25-0.40%, Si 1.50-2.50%, Mn 2.0-3.0%, Al 0.03-0.06%, P≤0.02%, S≤0.01%, N≤0.01% and at least one of 0.1-1.0% Cr and 0.1-0.5% Mo, and it also contains at least one of 0.01-0.1% Nb, 0.01-0.2% V and 0.01-0.05% Ti, and the balance is Fe and other inevitable impurities. The manufacturing method includes the following steps: 1) smelting and casting; 2) hot rolling; 3) pickling; 4) cold rolling; 5) continuous annealing: heating the strip to an absorptive temperature of 800-900°C, keeping the temperature for more than 60 seconds, then cooling to 150-300°C at a rate of 30-80°C / s, then heating to 350-440°C, keeping the temperature for 30-300 seconds, and finally cooling to room temperature. The microstructure of the product has 5-20% of retained austenite and 70-90% of martensite, with a tensile strength of more than 1500MPa and excellent formability.
[0008] Focusing on the field of 1500MPa ultra-high strength steel with short-process technology, there are relatively few related patents.
[0009] Chinese patent publication number CN111455282B discloses "quenching and partitioning steel with tensile strength ≥1500MPa produced by short process and method", whose components include: C 0.26-0.34%, Si 1.9-2.7%, Mn 2.6-3.4%, Ti 0.02-0.07%, Als 0.02-0.05%, P≤0.018%, S≤0.004%, N≤0.006%, O≤30ppm; its manufacturing process includes: molten iron desulfurization, smelting, argon blowing, LF refining, soft blowing, RH vacuum treatment, continuous casting, uniform heating of the cast ingot, descaling, seven-pass finishing rolling, laminar cooling, coiling, leveling, pickling, and continuous annealing. The steel strip Rel is 1000~1200MPa, Rm≥1500MPa, and elongation ≥15%. It is a method for producing 1500MPa grade quenching and partitioning steel using a short process. The composition of this patented steel is designed to be simple C, Si, Mn, Al, and Ti. Although this patent can obtain a good match of high strength and high plasticity, a series of problems such as steel leakage during thin slab continuous casting, slab surface cracks, and high risk of thin gauge rolling scrap due to the use of a high Si and high Mn composition system increase the manufacturing difficulty and cost of short-process production of ultra-high strength steel.
[0010] Chinese patent publication number CN114012056A discloses "a 1500MPa grade hot-formed steel and its preparation method", whose composition is: C 0.19-0.26%, Si 0.05-1.3%, Mn 0.9-2.1%, P≤0.015%, S≤0.002%, Alt 0.02-0.12%, B 0.002-0.020%, Cr 0.15-2.0%, Ti 0.02-0.15%, N≤0.006%, V+Nb≤0.15%, and the balance contains Fe and unavoidable impurities. The molten steel is smelted and continuously cast, then heat treated, descaled before rough rolling, rough rolling, electromagnetic induction heating, descaling before finishing rolling, finishing rolling, laminar cooling, coiling, air cooling to room temperature and pickling, and the pickled plate is obtained and then the pickled plate is hot stamped to obtain 1500MPa grade hot-formed steel with an elongation of less than 10%. This patent also uses a short process to produce hot-formed steel. The composition design of the steel is relatively complex and contains more alloy elements. Although the manufacturing method is relatively simple, it belongs to the field of hot-formed ultra-high strength steel, and the elongation of the material is insufficient. Summary of the invention
[0011] The purpose of the present invention is to provide a high-plasticity 1500MPa grade ultra-high strength steel and a manufacturing method thereof. The ultra-high strength steel has very excellent strength and plasticity, excellent surface quality, good welding performance, and a relatively simple composition without excessive alloy elements, and a simple and efficient manufacturing process; its yield strength is 1000-1300MPa, the tensile strength is ≥1500MPa, and the elongation at break is ≥18%; it has good application prospects in automotive safety structural parts, and is particularly suitable for manufacturing vehicle structural parts and safety parts with complex shapes and high requirements on forming performance, such as A / B pillars, door anti-collision bars, longitudinal beams, bumpers, etc.
[0012] To achieve the above object, the technical solution of the present invention is:
[0013] A high-plasticity 1500MPa grade ultra-high strength steel, the weight percentage of its components is:
[0014] C: 0.35-0.40%;
[0015] Si: 1.0~1.8%;
[0016] Mn: 1.5-2.0%;
[0017] Cr: 0.3~0.6%;
[0018] Al: 0.02~0.05%;
[0019] Ti: 0.02~0.05%;
[0020] B: 0.002~0.02%;
[0021] The balance includes Fe and other unavoidable impurities; and, at the same time, meets:
[0022] Carbon equivalent C in peritectic reaction zone eq1 >0.17%, C eq1 =C-0.03Mn-0.06Si-0.222S-0.04P;
[0023] Welding carbon equivalent C eq2 ≤0.56%, C eq2 =C+Mn / 20+Si / 30+2P+4S.
[0024] Preferably, the balance is Fe and other inevitable impurities.
[0025] Preferably, the C content is 0.36-0.38 wt%.
[0026] Preferably, the Si content is 1.4-1.7 wt%.
[0027] Preferably, the Mn content is 1.7-2.0 wt%.
[0028] Preferably, the Cr content is 0.4-0.6 wt%.
[0029] Preferably, among the other inevitable impurities: P≤0.015wt%, S≤0.002wt%, O≤0.002wt%, N≤0.004wt%.
[0030] The ultra-high strength steel of the present invention has a yield strength of 1000-1300 MPa, a tensile strength of ≥1500 MPa, and an elongation at break of ≥18%.
[0031] In the composition design of the ultra-high strength steel of the present invention:
[0032] The present invention makes full use of the influence of C, Si and Mn elements on the phase change of materials. At the same time, based on improving the production stability of thin slab continuous casting and rolling, the carbon equivalent of the components avoids the peritectic reaction zone, thereby achieving the purpose of improving the surface quality of the hot-rolled plate. By matching Cr and B with low Si and low Mn to improve the strength, an ultra-high-strength steel plate product with excellent strength, plasticity and surface quality is finally achieved.
[0033] C: C is the most important solid solution strengthening element and is extremely critical for ensuring strength. The higher the mass percentage of C element in steel, the greater the fraction of retained austenite, and the higher the enrichment of C in the retained austenite during partitioning, which is beneficial to enhancing the stability of retained austenite, producing the TRIP effect, and improving the ductility of the material. However, too high a C content in steel will reduce the weldability of the steel. When the mass percentage of C in the steel exceeds 0.40%, more twins are likely to appear after quenching, increasing crack sensitivity. Based on this, in the present invention, the C content is controlled between 0.35 and 0.40wt%, preferably controlled between 0.36 and 0.38wt%.
[0034] Si: Si can strongly inhibit the formation of cementite during the partitioning process, promote the enrichment of carbon into the residual austenite, and improve the stability of the residual austenite. The Si content required to effectively inhibit cementite is at least 1.0%. It should be noted that if the Si content in the steel is too high, it will reduce the high-temperature plasticity of the steel, greatly increase the risk of cracks in the casting during the thin slab continuous casting process, and even leak steel. At the same time, when the Si content is too high, stable oxides will be formed on the surface of the steel plate, which will have an adverse effect on the subsequent pickling process. Based on this, in the present invention, the Si content is controlled between 1.0 and 1.8wt%, preferably controlled between 1.4 and 1.7wt%.
[0035] Mn: Mn can expand the austenite phase area, reduce Ms and Mf points, improve austenite stability and hardenability of steel, and Mn is also an important solid solution strengthening element, which has a great influence on the strength of steel. However, it should be noted that too high Mn content in steel will lead to increased latent heat of solidification, especially for thin slab continuous casting, which will lead to limited heat transfer and too thin slab shell, greatly increasing the risk of cracks and even steel leakage in the thin slab continuous casting process, and affecting the production stability of short-process production of ultra-high strength steel. At the same time, if the Mn element content is too high, it will deteriorate corrosion resistance and welding performance. Based on this, in the present invention, the Mn content is controlled between 1.5 and 2.0wt%, preferably controlled at 1.7 to 2.0wt%.
[0036] Cr: Cr also plays a role in supporting strength. Especially for the present invention, since it is necessary to ensure the stability of the thin slab continuous casting and rolling process and control the Si and Mn contents, Cr is a key strength supplement element. Cr can improve the hardenability of steel and reduce the martensite transformation temperature. At the same time, it helps to refine the austenite grains and improve the strength during rolling. When the Cr content is lower than 0.3, it is difficult to ensure the strength, and when it is higher than 0.6, it will affect the welding performance of the material. Based on this, in the present invention, the Cr content is controlled between 0.3 and 0.6wt%, preferably controlled at 0.4 to 0.6wt%.
[0037] Al: When Al exists in solid solution, it can inhibit cementite precipitation and γ-to-martensite transformation, and improve austenite stability; and Al can form fine dispersed insoluble particles with C and N, which can refine grains. However, if the mass percentage of Al in steel is too high, a large amount of oxide inclusions will be easily formed, which is not conducive to the cleanliness of molten steel. Therefore, in the present invention, the Al content is controlled at 0.02-0.05wt%.
[0038] Ti: Ti can fix nitrogen in steel to form stable compounds, improve the quality of the ingot and corner crack defects. It can also form fine carbides to prevent the growth of austenite grains and refine the grains. However, if it is higher than 0.05% as defined in the present invention, it is not conducive to the enrichment of C in the residual austenite and the stabilization of the residual austenite; if it is lower than 0.02% as defined in the present invention, the crack incidence rate will increase. Therefore, the Ti content in the present invention needs to be controlled at 0.02-0.05%.
[0039] B: Its main function is to improve the hardenability of steel and the strength of steel. B is easy to segregate at the austenite grain boundary, delaying the transformation of austenite to ferrite. A lower content has a significant effect. At the same time, B has a good grain boundary purification effect, which can hinder the segregation of harmful elements at the grain boundary to a certain extent, thereby improving the deformation coordination of the material. However, too high a mass percentage of B will cause the strength of the steel to increase, which is not conducive to obtaining good shaping. Therefore, the B content in the present invention needs to be controlled in the range of 0.002 to 0.02%.
[0040] Among the other inevitable impurities described in the present invention: P≤0.015wt%, S≤0.002wt%, O≤0.002wt%, N≤0.004wt%.
[0041] In the above scheme, P, S, O, and N are all impurity elements. Although P can play a role in solid solution strengthening, inhibit carbide formation, and is beneficial to improving the stability of retained austenite, a too high mass percentage of P will weaken the grain boundary, increase the brittleness of the material, and deteriorate the welding performance. In other words, the positive effect of the P element is weaker than its negative effect. Therefore, it is preferred to control the mass percentage of P to P≤0.015wt%. As for N, since a too high mass percentage of N will bring difficulties to steelmaking and continuous casting, and is not conducive to inclusion control, it is preferred to control the mass percentage of N to N≤0.004wt%. Accordingly, if the S content in steel is too high, the plasticity of the material will be significantly deteriorated. For ultra-high strength steel, the S content should be strictly controlled, so the S content is controlled to S≤0.002wt%. The linear defects and surface peeling defects of ultra-high strength steel are mainly caused by the presence of Al2O3 and other types of inclusions under the skin of the continuous casting slab. Therefore, in order to improve the surface quality of the finished strip steel, it is necessary to reduce the deoxidation inclusions in the steel and control the O content in steelmaking. Therefore, the present invention controls the O content to O≤0.002wt%.
[0042] In addition, the composition content of the ultra-high strength steel of the present invention must also meet the following requirements:
[0043] Carbon equivalent C in peritectic reaction zone eq1 >0.17%, C eq1 =C-0.03Mn-0.06Si-0.222S-0.04P;
[0044] Welding carbon equivalent C eq2 ≤0.56%, C eq2 =C+Mn / 20+Si / 30+2P+4S.
[0045] This is because: when the carbon equivalent of molten steel is in the peritectic reaction zone and the peritectic reaction occurs, the liquid phase of the molten steel reacts with the δ phase to form the γ phase. During this process, the solidification of the molten steel will produce a very obvious volume shrinkage (about 4.7%). This feature is more likely to cause surface cracks and other defects in the thin slab continuous casting, and in severe cases, it may even cause steel leakage. eq1 The range is 0.08~0.17%. For high carbon ultra-high strength steel, the composition needs to be designed so that the carbon equivalent C eq1 Only when it is higher than 0.17 can the peritectic reaction be avoided; at the same time, from the empirical formula, the increase of Si and Mn element content makes it easier for the components to enter the peritectic reaction zone, thus affecting the surface quality of the final product.
[0046] In addition, the present invention has found through a large number of studies that when the mass percentages of C, Si, Mn, P and S meet the welding carbon equivalent C eq2 When the welding carbon equivalent C is less than 0.56%, the high-strength welding performance is better, and at the same time, the solid solution and microstructure strengthening effects of the material under this composition are better, and the material strength is higher. eq2 When the content of Zn is greater than 0.56%, the welding performance of the material will be significantly deteriorated.
[0047] The microstructure of the ultra-high strength steel of the present invention is 10% to 15% ferrite + 70% to 80% martensite + residual austenite.
[0048] In the ferrite of the ultra-high strength steel microstructure, grains below 5 μm account for more than 90%, and grains below 3 μm account for more than 60%.
[0049] The average grain size of the retained austenite in the ultra-high strength steel microstructure is ≤2 μm; and / or the average C content in the retained austenite is: 1.2wt%≤C(ra)≤2.0wt%.
[0050] This is because the presence of a certain amount of residual austenite in the material structure causes a phase transformation to martensite during deformation, resulting in the TRIP effect, which allows the material to have a tensile strength of 1500MPa while still having good plasticity. A certain amount of fine-grained ferrite can, to a certain extent, make the steel have better ductility among materials of the same level of strength, and can also contribute to part of the material strength due to the fine grain strengthening effect. However, if the content exceeds 15%, the tensile strength of the material is insufficient, and if it is less than 10%, it is difficult to meet the high plasticity requirements.
[0051] Martensite exists as the main hard phase in the material to ensure strength performance. When the content is less than 70%, the tensile strength of the material is insufficient, and when it is higher than 80%, it is difficult to ensure that there is enough residual austenite and ferrite to ensure plasticity. For ferrite grains, it is necessary to ensure that the grains are small enough to give full play to the fine grain strengthening effect, and at the same time, it is necessary to ensure the uniformity of ferrite structure and avoid abnormally large grains to improve the plasticity of the material. Therefore, it is necessary to control the proportion of grains below 5μm to more than 90%, and the proportion of grains below 3μm to more than 60%.
[0052] At the same time, for the retained austenite grains, the factors that affect the stability of the retained austenite during the deformation process mainly include the size of the retained austenite grains and the average C content in the retained austenite. When the retained austenite grain size is >2μm, the retained austenite size is too large and the stability is insufficient, which makes it easy to complete the TRIP effect in the early stage of deformation, resulting in insufficient plasticity of the material;
[0053] When the average C content in the retained austenite is less than 1.2wt%, the stability of the retained austenite is insufficient, and the retained austenite is prone to undergo martensitic transformation in the early stage of the deformation process, resulting in insufficient TRIP effect and failure to significantly improve the formability of the steel plate; when the average C content in the retained austenite is greater than 2wt%, the retained austenite is too stable and cannot undergo martensitic transformation during the deformation process, which also results in insufficient TRIP effect and the formability of the steel plate cannot be improved.
[0054] The manufacturing method of ultra-high strength steel described in the present invention is aimed at the current problems of thickness precision control and plate shape control of rolled hard plates in the cold rolling process of ultra-high strength steel, especially 1500MPa ultra-high strength steel, and the stringent rolling force requirements of ultra-high strength steel rolling on cold rolling units. Thin slab continuous casting and rolling of 1500MPa ultra-high strength steel are creatively adopted to directly obtain hot-rolled coils with finished thickness, and then the hot coils are treated with a heat preservation cover, so that the uniformity of the microstructure and performance of the hot coils is greatly improved, and the internal stress of the material is also eliminated to avoid abnormal brittle fracture in subsequent processes. After the heat preservation cover treatment, pickling is carried out, and the bottleneck process of cold rolling in the conventional process is eliminated, and the final continuous annealing treatment is directly carried out; at the same time, due to the use of thin slab continuous casting technology, it has inherent advantages in microstructure uniformity and segregation control, and due to the characteristics of hot delivery of thin slab continuous casting billets, a small amount of fine-grained ferrite can be maintained in the microstructure, and the elongation of the obtained ultra-high strength steel can be significantly improved under the same strength conditions.
[0055] Specifically, the method for manufacturing the high-plasticity 1500MPa grade ultra-high strength steel of the present invention comprises the following steps:
[0056] 1) Smelting and casting
[0057] According to the above composition, smelting is performed and cast into slabs, preferably thin slab continuous casting is adopted, the slab thickness at the continuous casting outlet is controlled to be 55-60 mm, and the continuous casting speed is controlled to be 2-5 m / min;
[0058] 2) Slab heating
[0059] Heating temperature 1200 ~ 1300 ℃, furnace time 25 ~ 40min;
[0060] 3) Hot rolling and cooling
[0061] First, high-pressure descaling is performed, and the final rolling temperature is controlled at 860-930°C. Then, laminar cooling is performed, and the cooling rate is controlled at 20-40°C / s, and the steel is cooled to 500-600°C for coiling.
[0062] 4) Slow cooling treatment
[0063] After the hot rolled coil is coiled, it is unrolled and sealed online with a heat preservation cover or transferred to a sealed heat preservation cover for slow cooling. After the heat preservation cover is treated for more than 4 hours, the cover can be opened to take out the hot rolled coil; preferably, after the hot rolled coil is coiled, it is sealed online with a heat preservation cover or transferred to a sealed heat preservation cover for slow cooling after waiting on the coil for more than 3 minutes;
[0064] 5) Pickling
[0065] The pickling speed is controlled at 60-150m / min;
[0066] 6) Annealing
[0067] Continuous annealing is adopted with an annealing temperature of 820-900°C, and slowly cooled to 690-760°C at a cooling rate of 3-10°C / s to obtain a certain proportion of ferrite; then quickly cooled to 150-250°C at a cooling rate of 50-100°C / s to partially transform austenite into martensite; then heated to 360-460°C, kept warm for 100-400s, and finally cooled to room temperature.
[0068] Preferably, in step 1), the leakage rate of thin slab continuous casting is controlled to be ≤1%, and the crack correction rate is controlled to be ≤1.2%.
[0069] Preferably, in step 6), the annealing temperature is 840-870°C; slowly cooled to 700-730°C at a cooling rate of 3-10°C / s; rapidly cooled to 170-230°C; and then heated to 400-430°C after rapid cooling, and kept warm for 150-300s.
[0070] Preferably, the volume content of hydrogen in the reducing atmosphere in the continuous annealing furnace is controlled to be 10-15%.
[0071] Preferably, in step 3), during high-pressure descaling, the water pressure of the first descaling pass is controlled to be not less than 260 bar, and the water pressure of the second descaling pass is controlled to be not less than 340 bar.
[0072] Preferably, the coiling in step 3) adopts a U-type coiling method, that is, the coiling temperature is controlled at 550-650° C. within a distance of ≤30 m between the head and the tail of the strip.
[0073] In the method for manufacturing ultra-high strength steel of the present invention:
[0074] The continuous casting described in the present invention preferably adopts thin slab continuous casting. Since the alloy elements in ultra-high strength steel are relatively high and the continuous casting process is not stable enough, especially the solidification latent heat is high and the shell is thin, the thin slab continuous casting pulling speed needs to be controlled at a low level. When the pulling speed exceeds 5m / min, problems such as liquid level fluctuation and steel leakage are prone to occur during the continuous casting process. However, the pulling speed cannot be too low to affect the production efficiency. Therefore, it is appropriate to control it at 2-5m / min.
[0075] At the same time, due to the use of thin slab continuous casting, the rough rolling process can be omitted, the hot rolling deformation can be reduced, and the final product specifications can be obtained more easily. Thin slab continuous casting can reduce the energy consumption required for heating by making full use of the heat of the slab and directly charging the slab into the heating furnace without waiting for the slab to completely cool to room temperature. At the same time, due to the lack of a cooling and then heating phase change process, the hot-rolled high-temperature structure is more uniform, and a more uniform ferrite or ferrite + pearlite structure is obtained after hot rolling, which is beneficial to maintaining a small amount of fine-grained ferrite in the microstructure of the finished product during annealing, improving the uniformity of the structure, and helping to improve plasticity.
[0076] During the heating of the slab, the thin continuous casting slab is first heated at high temperature in the full austenite zone for a period of time to soften the material and fully diffuse the composition. And try to use high temperature and short time treatment to simultaneously meet the uniform composition of ultra-high strength steel and avoid the problem of excessively thick oxide scale. The heating temperature cannot exceed 1300℃, which may cause the problem of grain boundary overburning. At this time, the heating time can be shortened to 25min to facilitate the control of oxide scale; if the heating temperature is lower than 1200℃, it will take more time to achieve uniform composition, which is also not conducive to the subsequent control of oxide scale.
[0077] Slab dephosphorization: After the slab is removed from the heating furnace, it is first subjected to two passes of high-pressure water dephosphorization to remove the soft iron oxide scale on the surface of the ingot as much as possible. After further rolling to the required thickness, a uniform and fine recrystallized material structure is formed. When the finishing rolling temperature is less than 860°C, ferrite will precipitate during the final rolling, which will easily make the hot-rolled state strength insufficient and thus affect the subsequent cold rolling annealing performance. Considering the upper limit control of the slab heating temperature and the temperature drop during rolling, the finishing rolling temperature generally does not exceed 930°C. Controlling the cooling rate at 20-40°C / s during laminar cooling is to avoid the formation of too much bainite or even martensite during the cooling process to ensure that the hot-rolled coiling state structure is mainly uniform ferrite + pearlite. The hot rolling coiling temperature is one of the most critical processes that affect the hot rolled state performance. When the coiling temperature is higher than 600℃, internal oxidation of Si and Mn is easy to occur on the surface of the steel plate, and a surface broken layer will be generated by pickling, which will affect the surface quality of the final product. However, since the fine-grained ferrite structure needs to be maintained in the hot rolled state, the coiling temperature cannot be too low and needs to be controlled above 500℃. The main reason for using U-type coiling to increase the coiling temperature at the head and tail during the coiling process is that the temperature drop at the head and tail of ultra-high strength steel is large and phase transformation is easy, resulting in a higher strength than in the coil. At the same time, increasing the coiling temperature is also conducive to reducing the strength of the strip head, making it easier to coil.
[0078] Controlling the thickness of the oxide scale on the surface of the steel strip after hot rolling to be ≤6μm, and the content of (FeO+Fe3O4) in the oxide scale on the surface of the steel strip after hot rolling to be ≤30wt%, can facilitate the subsequent step (5) and have an important influence on the performance of the steel plate obtained after continuous annealing. This is because: in the technical solution described in the present invention, FeO and Fe3O4 are more difficult to pickle than Fe2O3, and controlling the thickness of the oxide scale on the surface of the steel strip after hot rolling and the content of (FeO+Fe3O4) in the oxide scale on the surface of the steel strip after hot rolling to be ≤30wt% can improve the pickling effect and obtain a pickled plate surface that can be used for direct continuous annealing. Since the pickled plate can be directly subjected to continuous annealing, the deformation of the hot-rolled structure is small, and the steel plate structure is mainly ferrite and pearlite or bainite. Therefore, under the same continuous annealing conditions, the material strength can be reduced, the structure can be made more uniform, and excellent ductility can be obtained.
[0079] After coiling, let the steel coil wait on the reel for more than 3 minutes before unwinding. This is mainly to allow the inner ring of the steel coil to complete the bainite phase transformation to prevent the hot coil from flattening after unwinding. This is because for ultra-high-strength steel, the temperature of the inner ring drops faster during coiling, causing it to gradually enter the bainite temperature range during the coiling process and undergo bainite phase transformation, resulting in volume expansion. At this time, due to the different temperature drop rates of the inner and outer rings, the bainite phase transformation expansion is also different, so it is necessary to place it on the reel for more than 3 minutes to complete the bainite phase transformation, so that the volume change of the entire steel coil can be effectively differentiated under the support of the reel, thereby avoiding the hot coil flattening after unwinding.
[0080] After hot rolling, the heat preservation cover treatment can make the steel coil cool slowly as a whole to improve the uniformity of performance and organization. At the same time, the slow cooling process is also the process of releasing the thermal stress of the material, which is conducive to the stability of the subsequent material processing process to avoid extreme situations such as brittle fracture. The treatment time is more than 4 hours to completely release the internal stress, but the time should not be too long so as not to affect the production rhythm.
[0081] In the manufacturing method of the present invention, if the pickling speed is too fast, it will lead to under-pickling and fail to clean the inner oxide layer of the steel plate, resulting in color difference, while if it is too slow, it will lead to over-pickling, affecting the surface quality of the pickled plate and affecting the production efficiency. Therefore, it is advisable to control it within 60-150m / min.
[0082] In the manufacturing method of the present invention, the continuous annealing controls the annealing temperature to 820-900°C, which can form a homogenized austenite structure or austenite + ferrite structure; then slowly cools to 690-760°C at a cooling rate of 3-10°C / s to further adjust the ferrite content in the structure and improve the plasticity of the material; then cools to 150-250°C (i.e., between Ms and Mf temperatures) at a rate of 50-100°C / s, because: to ensure that only martensitic phase transformation occurs during the cooling process, the critical cooling rate must be no less than 50°C / s, and if the cooling rate exceeds 100°C / s, the production cost will increase significantly. At this time, most of the austenite is basically transformed into martensite, ensuring that the steel has a high strength; reheat to 360-460℃ and keep warm for 100-400s, so that carbon is partitioned in martensite and austenite, forming a certain amount of carbon-rich residual austenite, which is stably maintained at room temperature. Due to the TRIP effect, the work hardening ability and formability of the steel can be significantly improved, and an ultra-high strength steel plate with excellent plasticity can be obtained. The above partitioning process is set in this way because: when the reheating temperature is lower than 360℃ or the reheating time is less than 100s, the stabilization process of the residual austenite in the steel is not sufficient, and the residual austenite content obtained at room temperature will be insufficient; when the reheating temperature is higher than 460℃ or the reheating time is more than 400s, the steel undergoes obvious tempering softening, which will cause a significant decrease in the final material strength.
[0083] Preferably, in the continuous annealing process of step 6) of the present invention, the annealing temperature is 840-870°C; slowly cooled to 700-730°C at a cooling rate of 3-10°C / s; quickly cooled to 170-230°C; after quickly cooling, heated to 400-430°C and kept warm for 150-300s; and the volume content of hydrogen in the reducing atmosphere in the continuous annealing furnace is controlled to be 10-15%.
[0084] Since the ultra-high strength steel of the present invention adopts the composition design of high C and alloying of Mn, Si, Cr, and B and the ferrite grain refinement mechanism, during the continuous annealing process, the nucleation points of the reverse phase transformation of austenite increase while the size is further refined, and the average grain size of the residual austenite stably maintained at room temperature can be ≤2μm; the average C content in the residual austenite is ≥1.2%. In addition, since the material still contains a certain amount of Si, the martensite formed by rapid cooling is basically not decomposed during the partitioning process, so as to ensure the content of martensite in the organization, and then ensure the strength of the steel.
[0085] Compared with the prior art, the advantages of the present invention are:
[0086] 1. The composition design of the ultra-high strength steel described in the present invention is unique, which is different from the composition design ideas of existing patents.
[0087] The composition designs in existing patents are mostly complex, containing more alloy elements (such as Mo, V, Nb, Ni and even rare earth elements, etc.), and mostly showing the composition characteristics of high Si and high Mn.
[0088] The component design of the present invention is simple and unique, and fully utilizes the influence of C, Si, and Mn elements on the phase change of the material. At the same time, based on improving the production stability of thin slab continuous casting and rolling, the component carbon equivalent is avoided in the peritectic reaction zone to improve the surface quality, and the welding carbon equivalent is controlled to obtain excellent welding performance. Cr and B are matched by low Si and low Mn to ensure strength, and finally an ultra-high strength steel plate product with excellent strong plasticity, surface quality and welding performance is achieved.
[0089] 2. The manufacturing method of the present invention is also unique and different from the manufacturing method of the existing patent.
[0090] Most of the existing patents are conventional continuous casting + hot rolling + pickling + cold rolling + continuous annealing / hood annealing production processes. The process is lengthy and there are problems with cold-rolled plate shape and thickness accuracy for ultra-high-strength steel.
[0091] The present invention creatively proposes to adopt an efficient process flow of thin slab continuous casting + precision hot rolling + slow cooling treatment + pickling + continuous annealing, which can avoid the cold rolling bottleneck process of ultra-high strength steel, and at the same time has inherent advantages in terms of organizational uniformity, segregation control and manufacturing cost; and due to the characteristics of hot delivery of thin slab continuous casting billets, a small amount of fine-grained ferrite can be maintained in the organization, and the elongation of the obtained ultra-high strength steel can be significantly improved under the same strength conditions. In addition, it also leads to an increase in the nucleation points of the reverse phase transformation of austenite during continuous annealing, and further refinement of the size, and finally obtains a very fine and uniform mixed organization of martensite, ferrite and residual austenite. This organization has obvious advantages in plasticity over products of the same level while ensuring strength.
[0092] The ultra-high strength steel obtained by the present invention will have good application prospects in automobile safety structural parts, and is particularly suitable for manufacturing vehicle structural parts and safety parts with complex shapes and high requirements on forming performance, such as A / B pillars, door anti-collision bars, longitudinal beams, bumpers, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0093] Figure 1 This is a microstructure photograph of the ultra-high strength steel of Example 4 of the present invention.
[0094] Figure 2 This is an EBSD photograph of the phase composition of the ultra-high strength steel of Example 4 of the present invention. DETAILED DESCRIPTION
[0095] The present invention will be further described below in conjunction with embodiments and drawings.
[0096] Table 1 lists the composition of the steel of the embodiment of the present invention and the comparative example, and the balance includes Fe and other inevitable impurities except P, S, O, and N. Table 2 and Table 3 show the manufacturing process parameters of the steel of the embodiment of the present invention and the comparative example.
[0097] Comparative Examples 1-3 were obtained by conventional manufacturing process.
[0098] Among them, the C content of Comparative Example 1 exceeds the lower limit of the design range of the present invention, and its peritectic reaction zone carbon equivalent also falls into the peritectic reaction zone; the Si and Mn of Comparative Example 2 both exceed the upper limit of the design range of the present invention, and its peritectic reaction carbon equivalent and welding carbon equivalent also do not meet the design requirements of the present invention; although the peritectic reaction carbon equivalent and welding carbon equivalent of Comparative Example 3 both meet the requirements, the Si and Cr contents both exceed the lower limit of the design range of the present invention, which will result in insufficient material performance.
[0099] The comparative examples in Table 2 differ from the embodiments mainly in the continuous casting speed, slab heating temperature and time, final rolling temperature and curling temperature, and heat preservation cover treatment time.
[0100] The comparative examples in Table 3 are different from the embodiments mainly in pickling rate, annealing process, rapid cooling rate, partitioning temperature and time.
[0101] Table 4 lists the mechanical property test results of the ultra-high strength steels with excellent plasticity of Examples 1-20 and the comparative steels of Comparative Examples 1-3, as well as the steel leakage rate and crack correction rate of thin slab continuous casting under the conditions of the corresponding embodiments, wherein the mechanical properties are tested using ISO6892:1998 (room temperature tensile test method for metal materials) and P14 (A50) tensile specimen standards.
[0102] It can be seen from Table 4 that the ultra-high strength steel with excellent plasticity of Examples 1-20 of the present invention has excellent control over ductility, stability of the continuous casting process and surface quality of the ingot while ensuring strength, and its yield strength YS is 1000-1300MPa, tensile strength TS≥1500MPa, and elongation at break ≥18%. At the same time, the steel leakage rate of thin slab continuous casting can be controlled to ≤1%, and the crack correction rate can be controlled to ≤1.2%.
[0103] Table 5 shows the microstructure observation results of the ultra-high strength steel with excellent plasticity of Examples 1-20 of the present invention. The specific detection method is as follows:
[0104] 1) The residual austenite fraction is quantitatively tested by XRD after taking a 10*10 mm sample from the steel plate and grinding and polishing it;
[0105] 2) The martensite phase ratio was quantitatively tested by taking a 10*10 mm sample from the steel plate, grinding and polishing it, and then performing EBSD testing;
[0106] 3) The ferrite grain size ratio and the average size of retained austenite are obtained by statistical analysis when the standardized IQ value is processed during EBSD quantitative analysis;
[0107] 4) Test method for C content in retained austenite: Assuming that the Mn and Al concentrations of each component phase in the steel plate structure have not changed, the lattice constant a is read using the XRD retained austenite diffraction peak data, and the empirical formula is: a = 0.3556 + 0.00452x C +0.000095x Mn +0.00056x Al Calculate, where X C , X Mn , X Al Represent the C, Mn and Al concentrations in retained austenite respectively.
[0108] From Table 4 and Table 5, it can be seen that the microstructure of the 1500 MPa grade ultra-high strength steel with excellent plasticity of Examples 1-20 of the present invention is 10% to 15% ferrite + 70% to 80% martensite + retained austenite, wherein the grains below 5 μm in the ferrite account for more than 90%, the grains below 3 μm account for more than 60%, and the average grain size of the retained austenite is ≤2 μm; and / or the average C content in the retained austenite is: 1.2wt%≤C(ra)≤2.0wt%.
[0109] This shows that the 1500MPa grade ultra-high strength steel with excellent plasticity in each embodiment of the present invention has a certain amount of fine-grained ferrite and sufficient residual austenite, and good structural uniformity. Therefore, each embodiment has excellent plasticity while ensuring high strength.
[0110] Figure 1 , Figure 2 They are respectively typical microstructure and phase composition EBSD photos of the ultra-high strength steel Example 4 of the present invention. As can be seen from the figure, the structure of the ultra-high strength steel of the present invention is uniform and fine and contains a large amount of fine dispersed retained austenite.
[0111] In summary, the composition design of the ultra-high strength steel described in the present invention is simple. It is based on carbon-silicon-manganese steel and only adds Cr and B as alloy strengthening elements. Due to the composition characteristics of low Si and low Mn, the peritectic reaction in the continuous casting process can be avoided, thereby greatly improving the production stability of the continuous casting process, and the obtained product has excellent surface quality.
[0112] At the same time, the present invention creatively proposes an efficient process flow of thin slab continuous casting + precision hot rolling + slow cooling treatment + pickling + continuous annealing, which can avoid the cold rolling bottleneck process of ultra-high strength steel, and has inherent advantages in terms of organizational uniformity, segregation control and manufacturing cost. The obtained ultra-high strength steel can significantly improve the elongation under the same strength conditions, and will have good application prospects in automotive safety structural parts. It is particularly suitable for manufacturing vehicle structural parts and safety parts with complex shapes and high requirements for forming performance, such as A / B pillars, door anti-collision bars, longitudinal beams, bumpers, etc. The use of thin slab continuous casting and rolling short-process technology can directly obtain hot-rolled coils with the required finished thickness (0.8-2.0mm), and the cold rolling process is omitted accordingly, which greatly improves energy conservation and consumption reduction and production efficiency.
[0113] It should be noted that the prior art in the protection scope of the present invention is not limited to the embodiments given in the present application documents. All prior art that does not contradict the scheme of the present invention, including but not limited to prior patent documents, prior public publications, prior public uses, etc., can be included in the protection scope of the present invention.
[0114] In addition, the combination of the various technical features in the present invention is not limited to the combination described in the claims of the present invention or the combination described in the specific embodiments. All technical features described in the present invention can be freely combined or combined in any way unless there is a contradiction between them.
[0115] It should also be noted that the above-listed embodiments are only specific embodiments of the present invention. Obviously, the present invention is not limited to the above embodiments, and similar changes or modifications made therewith can be directly derived or easily associated with the contents disclosed by those skilled in the art from the present invention, and all should belong to the protection scope of the present invention.
[0116]
[0117]
[0118]
[0119]
[0120]
[0121]
[0122]
[0123]
[0124]
Claims
1. A high-plasticity 1500MPa grade ultra-high strength steel, the weight percentage of which is: C:0.35~0.40%; Si: 1.0~1.8%; Mn: 1.5-2.0%; Cr:0.3~0.6%; Al:0.02~0.05%; Ti: 0.02~0.05%; B:0.002~0.02%; The balance includes Fe and other unavoidable impurities; and, at the same time, satisfies: Carbon equivalent C in peritectic reaction zone eq1 >0.17%, C eq1 =C-0.03Mn-0.06Si-0.222S-0.04P; welding carbon equivalent C eq2 ≤0.56%, C eq2 =C+Mn / 20+Si / 30+2P+4S; The microstructure of the ultra-high strength steel is 10% to 15% ferrite + 70% to 80% martensite + retained austenite; In the ferrite of the ultra-high strength steel microstructure, grains below 5 μm account for more than 90%, and grains below 3 μm account for more than 60%; The yield strength of the ultra-high strength steel is 1000-1300 MPa, the tensile strength is ≥1500 MPa, and the elongation at break is ≥18%.
2. The high-plasticity 1500MPa grade ultra-high strength steel according to claim 1, characterized in that: The balance is Fe and other inevitable impurities.
3. The high-plasticity 1500MPa grade ultra-high strength steel according to claim 1 or 2, characterized in that: The C content is 0.36-0.38wt%.
4. The high-plasticity 1500MPa grade ultra-high strength steel according to claim 1 or 2, characterized in that: The Si content is 1.4 to 1.7 wt%.
5. The high-plasticity 1500MPa grade ultra-high strength steel according to claim 1 or 2, characterized in that: The Mn content is 1.7-2.0 wt%.
6. The high-plasticity 1500MPa grade ultra-high strength steel according to claim 1 or 2, characterized in that: The Cr content is 0.4-0.6wt%.
7. The high-plasticity 1500MPa grade ultra-high strength steel according to claim 1 or 2, characterized in that: Among the other inevitable impurities: P≤0.015wt%, S≤0.002wt%, O≤0.002wt%, N≤0.004wt%.
8. The high-plasticity 1500MPa grade ultra-high strength steel according to claim 1, characterized in that: The average grain size of the retained austenite in the ultra-high strength steel microstructure is ≤2 μm; and / or, the average C content in the retained austenite is: 1.2wt%≤C(ra)≤2.0wt%.
9. The method for producing high-plasticity 1500 MPa grade ultra-high strength steel according to any one of claims 1 to 8, characterized in that: The steps include: 1) Smelting and casting According to the composition of the high-plasticity 1500MPa grade ultra-high strength steel, smelting is performed to cast into slabs, thin slab continuous casting is adopted, the slab thickness at the continuous casting outlet is controlled to be 55-60mm, and the continuous casting speed is controlled to be 2-5m / min; 2) Slab heating Heating temperature 1200 ~ 1300 ℃, furnace time 25 ~ 40min; 3) Hot rolling and cooling First, high-pressure descaling is performed, and the final rolling temperature is controlled at 860-930°C. Then, laminar cooling is performed, and the cooling rate is controlled at 20-40°C / s, and then the steel is cooled to 500-600°C for coiling. 4) Slow cooling treatment After the hot rolled coil is coiled, it is unrolled and sealed with an insulation cover online or transferred to a sealed insulation cover for slow cooling. After the insulation cover is treated for more than 4 hours, the cover can be opened to take out the hot rolled coil; 5) Pickling The pickling speed is controlled at 60-150m / min; 6) Annealing Continuous annealing is adopted, the annealing temperature is 820-900°C, and it is slowly cooled to 690-760°C at a cooling rate of 3-10°C / s; then it is quickly cooled to 150-250°C at a cooling rate of 50-100°C / s; then it is heated to 360-460°C, kept warm for 100-400s, and finally cooled to room temperature.
10. The method for manufacturing high-plasticity 1500MPa grade ultra-high strength steel according to claim 9, characterized in that: In step 1), the leakage rate of thin slab continuous casting is controlled to be ≤1%, and the crack correction rate is controlled to be ≤1.2%.
11. The method for manufacturing high-plasticity 1500MPa grade ultra-high strength steel according to claim 9, characterized in that: Step 3) During high-pressure descaling, the water pressure of the first descaling pass is controlled to be not less than 260 bar, and the water pressure of the second descaling pass is controlled to be not less than 340 bar.
12. The method for producing high-plasticity 1500 MPa grade ultra-high strength steel according to claim 9 or 11, characterized in that: Step 3) The coiling adopts a U-type coiling method, that is, the coiling temperature of the steel strip is controlled at 550-650°C within a distance of ≤30m between the head and the tail of the steel strip.
13. The method for manufacturing high-plasticity 1500MPa grade ultra-high strength steel according to claim 9, characterized in that: In step 4), after the hot rolled coil is coiled, it is kept on the coil for ≥3 minutes and then sealed online with a heat preservation cover or transported to a sealed heat preservation cover for slow cooling.
14. The method for manufacturing high-plasticity 1500MPa grade ultra-high strength steel according to claim 9, characterized in that: Step 6) In the annealing process, the annealing temperature is 840-870°C; slowly cooled to 700-730°C at a cooling rate of 3-10°C / s; quickly cooled to 170-230°C; after quickly cooling, heated to 400-430°C and kept warm for 150-300s.
15. The method for producing high-plasticity 1500 MPa grade ultra-high strength steel according to claim 9 or 14, characterized in that: Step 6) During the annealing process, the volume content of hydrogen in the reducing atmosphere in the continuous annealing furnace is controlled to be 10-15%.
Citation Information
Patent Citations
Preparation method of 1400mpa grade low yield ratio high elongation cold-rolled ultra-high-strength automotive steel
CN103667884B
A 1500MPa high-strength, high-ductility automotive steel and its manufacturing method
CN106244918B
A third-generation high-strength and tough steel for automobiles and its preparation method
CN106917055B
Method for producing quenched steel with tensile strength ≥1500MPa using a short process
CN111455282B
1500MPa-grade hot forming steel and preparation method thereof
CN114012056A
Cited By
Ultrahigh-strength steel plate with yield strength of 1,500 MPa for engineering machinery and manufacturing method of ultrahigh-strength steel plate
CN120758795A